2009
DOI: 10.1073/pnas.0810473106
|View full text |Cite
|
Sign up to set email alerts
|

Acute inflammatory proteins constitute the organic matrix of prostatic corpora amylacea and calculi in men with prostate cancer

Abstract: Corpora amylacea (CA) are a frequent microscopic finding in radical prostatectomy specimens from men undergoing treatment for prostate cancer. Although often observed histologically to be associated with inflammation, the contribution of CA to prostatitis-related symptoms of unknown etiology or to prostate carcinogenesis remains unclear. Prostatic calculi (PC), which potentially represent calcified forms of CA, are less common but can cause urological disease including urinary retention and prostatitis. We con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
107
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(122 citation statements)
references
References 42 publications
8
107
0
3
Order By: Relevance
“…3). CA stained very strongly for lactoferrin, showing an unstained ring structure, as expected (Sfanos et al 2009). Prostate from control and HFDC testosterone showed scanty positivity for lactoferrin (Fig.…”
Section: Effect Of Hfd and Hormonal Supplementation On Mets And Prostmentioning
confidence: 96%
See 1 more Smart Citation
“…3). CA stained very strongly for lactoferrin, showing an unstained ring structure, as expected (Sfanos et al 2009). Prostate from control and HFDC testosterone showed scanty positivity for lactoferrin (Fig.…”
Section: Effect Of Hfd and Hormonal Supplementation On Mets And Prostmentioning
confidence: 96%
“…Corpora amylacea are protein aggregates of lactoferrin (Sfanos et al 2009), delivered by neutrophils following acute prostate inflammation (Legrand et al 2005, Sfanos et al 2009). As expected (De Marzo et al 2007, Sfanos et al 2009, Yanamandra et al 2009), we have observed corpora amylacea adjacent to infiltrating inflammatory cells. Gene expression of macrophage, neutrophil, and CD4…”
Section: Discussionmentioning
confidence: 99%
“…Prostatic calculi are presumed to form by the precipitation of prostatic secretions and calcification o f t h e c o r p o r a a m y l a c e a u n d e r i n f l a m m a t o r y conditions [1,2]. The precise mechanisms by which calculi form and the association of calculi with benign and malignant conditions of the prostate gland are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…This discrepancy may be due in part to new and more appropriate methods available nowadays that allow the detection of chronic inflammation and infection with greater precision. Recently published studies showed that acute phase proteins predominated in the structure of prostatic stones [25,26] . In addition, bacterial biofilm was found in the prostatic stones and high frequency of bacterial imprints was found in these stones by electron microscopy scanning [27][28][29] .…”
Section: Discussionmentioning
confidence: 99%